Flooding of Sandy Beaches in a Changing Climate. The Case of the Balearic Islands (NW Mediterranean) - Agulles, Miguel; Jordà, Gabriel; Lionello, Piero (Frontiers in Marine Science, 2021)
The fate of the beaches around the world has paramount importance as they are one of the main assets for touristic activities and act as a natural barrier for coastal protection in front of marine storms. Climate change could put them at risk as sea levels rise and changes in the wave characteristics may dramatically modify their shape. In this work, a new methodology has been developed to determine the flooding of sandy beaches due to changes in sea level and waves. The methodology allows a cost-effective and yet accurate estimation of the wave runup for a wide range of beach equilibrium profiles and for different seagrass coverage. This, combined with regional projections of sea level and wave evolution, has allowed a quantification of the future total water level and coastline retreat for 869 beaches across the Balearic Islands for the next decades as a function of greenhouse gases emission scenario. The most pessimistic scenario (RCP8.5) at the end of the century yields an averaged percentage of flooded area of 66% under mean conditions which increases up to 86% under extreme conditions. Moreover, 72 of the 869 beaches of the region would permanently disappear while 314 would be completely flooded during storm episodes. Under a moderate scenario of emissions (RCP4.5), 37 beaches would permanently disappear while 254 would disappear only during storm episodes. In both cases, the average permanent loss of beach surface at the end of the century would be larger than 50%, rising over 80% during storm conditions. The results obtained for the Balearic Islands can be extrapolated to the rest of the Mediterranean as the beaches in all the regions have similar characteristics and will be affected by similar changes in sea level and wave climate. These projections indicate that adaptation plans for beach areas should be put in place as soon as possible.